Socioeconomic gradient in COVID-19 vaccination: evidence from Israel - Mor Saban (BMC, 2021)
Abstract Background Low socioeconomic status (SES) groups have been disproportionately affected by the COVID-19 pandemic. We aimed to examine COVID-19 vaccination rate by neighborhood SES and ethnicity in Israel, a country which has achieved high vaccination rates. Methods Data on vaccinations were obtained from the Israeli Ministry of Health’s open COVID-19 database, for December 20, 2020 to August 31, 2021. Correlation between vaccination rate and neighborhood SES was analyzed. Difference in vaccination rate between the first and second vaccine dose was analyzed by neighborhood SES and ethnicity. Findings A clear socioeconomic gradient was demonstrated, with higher vaccination rates in the higher SES categories (first dose: r = 0.66; second dose: r = 0.74; third dose: r = 0.92). Vaccination uptake was lower in the lower SES groups and in the Arab population, with the largest difference in uptake between Jewish and Arab localities for people younger than 60, and with the gap widening between first and third doses. Conclusions Low SES groups and the Arab ethnic minority demonstrated disparities in vaccine uptake, which were greater for the second and third, compared with the first vaccine dose. Strategies to address vaccination inequity will need to identify barriers, provide targeted information, and include trust-building in disadvantaged communities.